Linear static analysis of a steel roof truss - Nurulfatiha , Ismail (2013)
This thesis analyzed linear static analysis of a steel roof truss. When loads are applied to a body, the body will deformation and the effect of loads is transferred throughout the body. The external loads induce internal forces and reactions to turn the body into a state of equilibrium. This analysis is determined the stresses and displacements parameter of a roof truss. It also to determine the tensile, compressive and compression buckling in the critical section of a steel roof truss. Therefore, propose the best design of a steel roof truss. This thesis describes the finite element analysis consists of a model of a material or design that stressed and analyzed for specific results. It is used in new design products, and the existing of product refinement. In industry, there are generally had two types of analysis that are used; two dimensional modeling and three dimensional modeling. Usually two dimensional modeling conserves its simplicity and support the analysis to be executed on a relatively normal computer; it tends to produce less accurate results. The finite element model of steel roof truss a linear static was be analyzed. There are 6 model with different steel section is considered in order to get the most optimum result for the construction of a roof truss. All the steel section in equal L section and have the same yield strength which is 275NIrnrn 2 . From the results, it is observed that L angle section 150x 1 50 x 14 is adequate to applying on a roof truss. The roof truss can be considered as safe since the only design criteria that required in designing is tensile, compression and buckling. Furthermore, if all the steel section can pass all this three forces, the roof truss is considered as safe to be used. All the steel section is in a normal yield strength which is 275N1mm2.